A Multivariate Regression and Discriminant Canonical Analysis of Isometric Mid-Thigh Pull Performance in Cadet Inline Speed Skaters - Aedo-Munoz, E (Universidade da Beira Interior, 2022)
This study measured the peak force (PF) in cadet inline speed skaters (ISS) and verified the physical measures that determine athletes performance on the Isometric Mid-Thigh Pull Test (IMTP) through a multivariate regression and discriminant canonical analysis. A total of 36 high-performance male (n= 18; age= 17.4± 1.21 years; body mass= 65.1± 6.18 kg; height= 168.6± 5.1 cm) and female (n= 18; age= 17.4± 1.23 years; body mass= 55.5± 4.4 kg; height= 158.6± 5.2 cm) athletes were measured two times (with a 3-day interval). All participants performed the IMTP and sit-and-reach (SR) tests, and an evaluator performed anthropometric circumference measurements on their thighs and calves. The main results indicated that males showed a higher PF on the test (m= 59.0± 3.9 N/kg vs. f= 50.4± 5.8 N/kg; p≤ 0.001) and retest (m= 59.1± 4.2 N/kg vs. f= 51.9± 6.6 N/kg; p≤ 0.001). In the first, thigh circumference (X2= 29.01, p≤ 0.001, R2= 0.74) had an overall 91.7% prediction. The second model included using the SR and thigh circumference (X2= 49.91, p≤ 0.001, R2= 1.0) showed an overall prediction of 100.0%. The thigh circumference matrix showed better predictive power for (coefficient= 7.158) male and female IMTP performance. In conclusion, despite the gender differences, the thigh circumference is a good predictor for PF in cadet ISS athletes. © 2022 University of Beira Interior. All rights reserved.